Development of Learning Scenarios as Implementation of 21st Century Mathematic Skills in Madrasah Ibtidaiyah - Ikhtiati Ikhtiati; Nisa Aulia; Ahmad Sayuti Nainggolan; Hedia Milfa Rizki; Adzkya Milfa Laensadi (Edumaspul: Jurnal Pendidikan, 2023)
This study aims to describe the implementation of 21st century mathematical skills in Madrasah Ibtidaiyah. The research was conducted in the form of qualitative research to describe the implementation of 21st century mathematical skills using a learning scenario. The research was carried out at one of the MI schools in Jambi City which was conducted on teachers and students with a total of 102 students. Data collection was carried out through questionnaires, observation and interviews. The sample used is a non-probability sample with a purposive sampling technique which is a sampling technique with certain considerations. The research sample consisted of 6 teachers in class I-VI and 12 students in class I-VI. Interviews were conducted with MI teachers and students regarding the implementation of 21st century mathematical skills, then observations were carried out during the learning process and questionnaires were distributed to teachers to find out the implementation of 21st century mathematical skills. Furthermore, the data were analyzed using qualitative descriptive techniques through the Miless research design which consisted of collecting, presenting, reducing data and drawing conclusions. The results of the implementation of mathematical skills have gone well in MI Jambi City which are described in 3 stages (1) The teacher designs a learning scenario which contains 5 types of mathematical skills which will be laid out in detail in the lesson plan before learning is carried out (2) The learning implementation is adjusted to the scenario design and lesson plan that has been made by the teacher where each learning implementation raises 5 types of mathematical skills. (3) The implementation of the 5 types of mathematical skills found that students can reason well, communicate well, represent lessons well, and have good mathematical connections and have good problem solving